Analisis Dampak Jatuh Tegangan pada Saluran Transmisi 150 kV Gardu Induk Kendari New – Gardu Induk Puuwatu 150 kV - La Ode Masri Ande Kolewora; Hasmina Tari Mokui; Yuni Aryani Koedoes; Luther Pagiling; Tachrir; Achamd Nur Aliansyah; Mustamin; Gamal Abdel Nasser Maskki (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2024)
In today's era, people's need for electrical energy is increasing along with technological advances and increasing people's standard of living, so that electric energy has become a basic need for people in meeting their needs. As a provider of electricity PLN is required to meet the needs of the community for electric power efficiently and quality. The process of sending electrical power to consumers has a problem, especially when the drop voltage, this happens if the voltage at the base of the delivery with the voltage at the receiving end occurs a difference. The analysis was conducted to find out the magnitude of the drop voltage that occurred in the transmission line at Kendari New Substation - Puuwatu Substation 150 kV, as well as calculate the economic value due to the loss of electrical power. The calculation method is done using drop voltage equations and analysis using ETAP software. The reference standards for service voltage variations used are SPLN.1-1995 and IEEE 1159-1995. Based on the results of the study it can be concluded that: (1) The calculation manually the value of the drop voltage is 0.371 %; (2) The result of the simulation of drop voltage using ETAP software is 0.143 %; In accordance with the standards SPLN.1-1995 and IEEE 1159-1995 the drop voltage that occurred is still within the tolerable limit of less than 5%; (3) Calculation of economic losses due to loss of electricity during january to June amounted to Rp161,408,119.92